Analysis of The Role of Stakeholders in Efforts to Reduce the Acceleration of Stunting: A Case Study in a Quality Family Planning Village Locus - Dwi Noerjoedianto; Ismi Nurwaqiah Ibnu; Evi Wisudariani (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
West Tanjung Jabung Regency has succeeded in reducing the prevalence of stunting over the last three years. This is inseparable from the efforts of all sectors that play a role in innovation programs to reduce stunting. One of the efforts to accelerate stunting reduction is the program that has been implemented by Quality Family Village. This research aims to analyze stakeholders in their insights and roles in reducing stunting in quality family planning village loci. This research uses a qualitative approach with analytical descriptive methods. This research took place in West Tanjung Jabung Regency, which is the district with the highest percentage reduction in stunting prevalence in 2022. Data collection methods were in-depth interviews and observation. The informants in this research were 15 people consisting of the main informant and supporting informants. Data analysis using NVivo Software. The results of this research are that there are good practices characterized by local wisdom in efforts to reduce the acceleration of stunting cases in the form of jargon/slogans such as JAS BERKAH, Safari Subuh, and the Declaration of Stunting Free Villages. The roles of stakeholders consisting of facilitators, coordinators, accelerators, evaluators, and policy creators have been placed by the functions and roles of the Stunting Reduction Acceleration Team. The role of stakeholders related to the convergence action plan can be mapped into three scenarios, namely the role of the chairman in convergence actions 1 and 2, and the role of the regional secretary in convergence actions 2, 4, and 5. Meanwhile, the role of technical agencies focuses on convergence actions 4, 5, 6, 7, and action 8. It is necessary to carry out continuous coordination with all relevant stakeholders and increase maximum coordination on achievement indicators, as well as community support for active and independent participation. Keywords: Convergence action, family planning, stakeholders, stunting